From concentration camp to campus : Japanese American students and World War II - Austin, Allan W. (Asian American experience., 2004)
In the aftermath of Japan's attack on Pearl Harbor and the systematic exile and incarceration of thousands of Japanese Americans, the National Japanese American Student Relocation Council was born. Created to facilitate the movement of Japanese American college students from concentration camps to colleges away from the West Coast, this privately organized and funded agency helped more than 4,000 incarcerated students pursue higher education at more than 600 schools during WWII. Austin argues that the resettled students transformed the attempts at assimilation to create their own meanings and suit their own purposes, and succeeded in reintegrating themselves into the wider American society without sacrificing their connections to community and their Japanese cultural heritage.